An Experimental Study on Teaching Vocabulary for Reading Comprehension by Using Crossword Puzzles for the Eighth Grade Students at SMP Negeri 24 Banjarmasin. - Khatimah, Husna (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2018)
The purpose of this research is to find out whether there is any significant difference in studentsâ vocabulary achievement for reading comprehension taught by using crossword puzzles for the eighth-grade students at SMP Negeri 24 Banjarmasin. Therefore, the researcher employed quasi-experimental study and took class VIIIB (experimental group) and class VIIIE (control group), totally 64 students as the sample. In collecting data, the researcher used vocabulary test for reading comprehension, and observation. The findings of the research show that there is a significant difference in studentsâ vocabulary achievement for reading comprehension of students who are taught by using crossword puzzles. The difference can be seen from the studentsâ average scores; 70.18 in pre-test and 81.18 in post-test for experimental class and 70.03 in pre-test and 72.87 in post-test for control class. In addition, the t-test calculation showed that t-test (5.76) > t-table (1.99), which means Ha is accepted and Ho is rejected.Therefore, it is suggested for all English teachers to use crossword puzzles as one of the alternative media to teach vocabulary for reading comprehension, which can be used to help the studentsâ to improve their vocabulary for reading comprehension.